The Aesthetic Map of the North, 1845-1859 - MacLaren, I.S. (ARCTIC, 1985)
The aesthetics of the Sublime and the Picturesque comprised the perceptual baggage with which early nineteenth-century British explorers and travellers combed the globe. As important to their identification of space as measurements of longitude and latitude, these two schemata governed the ways in which the Canadian Arctic was described and depicted during the British search for a Northwest Passage from 1819 to 1859. During the last ten years of this period, when the majority of mariners travelled and resided in the arctic archipelago, more and more fanciful representations appeared on the aesthetic map that their writing and painting were charting. These more fanciful mappings opened a wider discrepancy between perception of landscape and environmental reality, which invited disastrous consequences for the searchers, but in the face of the growing realization that Franklin's crews had been consumed by the arctic nature, the need to mask the terror of the realm by invoking modes of describing and depicting European nature became paramount. The adaptation by means of the genial Sublime and the Picturesque of the land, rather than the traveller, if it did not provide what can be considered a realistic picture of the North today, nevertheless fortified British optimism and morale sufficiently to see the search for Franklin through to a successful conclusion.Key words: arctic exploration 1819-59, the Sublime, the Picturesque, aesthetic mapping Mots clés: l'exploration de l'Arctique canadien 1819-1859, le Sublime, le Pittoresque, la carte esthétique